Iowa Birdline update, January 16, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Email for the Iowa Birdline update for January 16, 1995. Highlights of the update include sightings of a Bohemian Waxwing, Cedar Waxwings, Long-eared Owl, Short-eared Owl and a Northern Goshawk. Also included are handwritten notes for the next week's update with sightings of three Trumpeter Swans and a Common Redpoll. Epson - sheet feed/flatbed